The role of adversity quotient (AQ) for successful mathematics learning - Siti Salamah Br Ginting (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
This study aims to explore the role of adversity quotient (AQ) in the success of mathematics learning. AQ refers to an individual's ability to survive and overcome difficulties in learning, which is particularly relevant in the context of mathematics which is often considered a challenging subject. This article examines the history and development of the concept of AQ, how it differs from other intelligences such as IQ and EQ, as well as AQ development strategies to improve achievement in mathematics. This study uses a literature review method by analyzing academic literature in the last 10-15 years. Challenges include the complexity of mathematical concepts, misunderstandings, anxiety, lack of motivation, diverse learning styles, a less supportive learning environment, and different starting abilities. AQ, which refers to a person's ability to persevere in the face of adversity, plays a crucial role in helping students overcome these challenges. This research discusses the history and development of the concept of AQ, its dimensions, its differences with other intelligences such as IQ and EQ, and its important role in overcoming the challenges of mathematics learning. The results of the study show that AQ contributes significantly to improving students' motivation, learning resilience, and problem-solving skills in mathematics. This study provides recommendations for educators in creating a supportive learning environment as well as strategies to improve students' AQ.